PENINGKATAN LITERASI INFORMASI SISWA SEKOLAH DASAR MELALUI MODEL DISCOVERY LEARNING - Wati, Sisna; Luthvi Azizah, Alif; Izzatika, Amrina; Mujiyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of students’ information literacy is indicated by difficulties in understanding question instructions, the tendency to copy information without analysis, and a lack of critical ability in selecting information sources. This study aimed to analyze the effect of the Discovery Learning model on students’ information literacy and to examine the differences in information literacy between the experimental and control classes of fifth-grade students at SDN 5 Metro Timur. This research employed a quasi-experimental method with a nonequivalent control group design. The population consisted of all fifth-grade students at SDN 5 Metro Timur totaling 41 students. The sample was determined using a saturated sampling technique, with class VB as the experimental class and class VA as the control class. Data were collected through test and non-test techniques. Data analysis used simple linear regression to determine the effect of the Discovery Learning model and an independent t-test to examine differences in information literacy between classes. The results indicated that the Discovery Learning model significantly improved students’ information literacy and showed a significant difference between the two classes.